Revisiting the sigma-1 receptor as a biological target to treat affective and cognitive disorders. (January 2022) - Sałaciak, Kinga; Pytka, Karolina
Highlights: Sigma-1 receptors are unique therapeutic targets modulating the activity of various proteins and systems in the organism. Preclinical studies reported that sigma-1 receptor expression correlates with the clinical manifestation of disease. Animal studies suggest that targeting sigma-1 receptors might effectively treat affective and cognitive disorders. Abstract: Depression and cognitive disorders are diseases with complex and not-fully understood etiology. Unfortunately, the COVID-19 pandemic dramatically increased the prevalence of both conditions. Since the current treatments are inadequate in many patients, there is a constant need for discovering new compounds, which will be more effective in ameliorating depressive symptoms and treating cognitive decline. Proteins attracting much attention as potential targets for drugs treating these conditions are sigma-1 receptors. Sigma-1 receptors are multi-functional proteins localized in endoplasmic reticulum membranes, which play a crucial role in cellular signal transduction by interacting with receptors, ion channels, lipids, and kinases. Changes in their functions and expression may lead to various diseases, including depression or memory impairments. Thus, sigma-1 receptor modulation might be useful in treating these central nervous system diseases. Importantly, two sigma-1 receptor ligands entered clinical trials, showing that this compound group possesses therapeutic potential. Therefore, based on preclinical studies, this review discusses whether the sigma-1 receptor could be a promising target for drugs treating affective and cognitive disorders.